2022
DOI: 10.26596/wn.20221345-14
|View full text |Cite
|
Sign up to set email alerts
|

Faster rehabilitation weight gain is associated with liver fat in adult survivors of childhood severe acute malnutrition

Abstract: BackgroundNutritional rehabilitation during severe acute malnutrition (SAM) aims to quickly restore a healthy body weight, but rapid weight gain has been associated with later cardiovascular risk. We hypothesized that faster weight gain during SAM rehabilitation and post-hospitalization is associated with liver fat in adult survivors.MethodJamaican adult survivors of childhood SAM underwent abdominal CT scan to estimate liver fat as mean liver attenuation (MLA) and liver spleen ratio (L/S). Birth weight (BW) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…However, while the tendency to store fat abdominally might be a persisting response to adverse conditions and growth failure in fetal life and infancy [ 29 ], we have shown this tendency to store fat in the abdominal compartment to be independent of minimum weight-for age z-score during hospitalization. Similarly, we recently reported that children who experienced faster weight gain during nutritional rehabilitation had greater liver fat as adults, and this relationship was independent of weight-for age z-score at admission [ 30 ]. Therefore, the association between rehabilitation weight gain in childhood and adult android fat in this group of young, normal-weight SAM survivors could signal an increased risk of clinical NCDs as they age.…”
Section: Discussionmentioning
confidence: 94%
“…However, while the tendency to store fat abdominally might be a persisting response to adverse conditions and growth failure in fetal life and infancy [ 29 ], we have shown this tendency to store fat in the abdominal compartment to be independent of minimum weight-for age z-score during hospitalization. Similarly, we recently reported that children who experienced faster weight gain during nutritional rehabilitation had greater liver fat as adults, and this relationship was independent of weight-for age z-score at admission [ 30 ]. Therefore, the association between rehabilitation weight gain in childhood and adult android fat in this group of young, normal-weight SAM survivors could signal an increased risk of clinical NCDs as they age.…”
Section: Discussionmentioning
confidence: 94%